Hubungan Kebiasaan Merokok dengan Status Kesehatan Jaringan Periodontal - Surya Nelis; Indah Edranovi Putri; Rizanda Machmud (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2015)
Smoking is one of the periodontal risk factors. Nicotin in cigarettes alters the immune response system and blood vessels in the dental tissue. Tar in cigarettes facilitates the accumulation of plaque. This combination causes periodontal tissue damage. The aim of study is to know the relationship of smoking and periodontal health status. This study was cross sectional study involved 80 smokers who were selected based on simple random sampling. This study used Community Periodontal Index (CPI). Data was analyzed using Chi-Square. The result showed that none of respondents with healthy periodontal health status. Smokers with duration of smoking <10 years, amount of smoking <20 rods/day and white cigarette smokers showed moderate periodontal health status. Smokers with duration of smoking >10 years, amount of smoking  >20 rods/day and kretek cigarette smokers showed poor periodontal health status. The conclusion of this study are significant relationship between amount of cigarette (p=0,000), duration of smoking (p=0,000, type of cigarette(p=0,006) and periodontal health status.